2022
DOI: 10.1039/d2ta03034a
|View full text |Cite
|
Sign up to set email alerts
|

Research progress of asymmetrically coordinated single-atom catalysts for electrocatalytic reactions

Abstract: Energy has increasingly become the material basis for the development of human society and occupies a strategic position in the national economy. Single-atom catalysts (SACs) are widely recognized as promising...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 126 publications
0
24
0
Order By: Relevance
“…In the second pyrolysis procedure, melamine and cyanuric acid, phytic acid, and l -alanine were nitrogen, oxygen, and carbon sources, respectively. Without phytic acid, only Cu SACs with typical Cu 1 –N 4 single sites were formed, and the maximum density of Cu atoms was less than 1 atoms/nm 2 . By adjusting the amounts of added Cu 2+ ions, a series of Cu SACs with various Cu densities can be obtained. The highest loading of Cu single atoms was 21.3 wt %, equivalent to a Cu density of 2.4 atoms/nm 2 (Table S1).…”
Section: Results and Discussionmentioning
confidence: 99%
“…In the second pyrolysis procedure, melamine and cyanuric acid, phytic acid, and l -alanine were nitrogen, oxygen, and carbon sources, respectively. Without phytic acid, only Cu SACs with typical Cu 1 –N 4 single sites were formed, and the maximum density of Cu atoms was less than 1 atoms/nm 2 . By adjusting the amounts of added Cu 2+ ions, a series of Cu SACs with various Cu densities can be obtained. The highest loading of Cu single atoms was 21.3 wt %, equivalent to a Cu density of 2.4 atoms/nm 2 (Table S1).…”
Section: Results and Discussionmentioning
confidence: 99%
“…The resolution of HADDF-STEM images can reach up to 1 Å, allowing a fine distinction between individual atoms [ 90 ]. For instance, Zhang et al reported a conception in which graphene defects capture Ni single atoms as active sites, as shown in Figure 3 a, and identified the presence of di-vacancy defects that trap an atomic Ni species (aNi@Di-vacancy) [ 91 ].…”
Section: The Characterization Of Asymmetric Atom Sitesmentioning
confidence: 99%
“…SACs have been reported as effective catalysts due to their four-coordinated M-N 4 active sites with a symmetric coordination environment. 131–134 Due to their adjustable geometry and electronic properties, and the high exposure of active sites, M-N 4 moieties are considered one of the main active sites for eCO 2 RR catalytic performance. Therefore, it can be concluded that different activity and selectivity of the products are mainly influenced by the nature of the central metal atoms.…”
Section: C1 Products On Mof-derived Sacsmentioning
confidence: 99%
“…However, theoretical and experimental results revealed that the high structure/electron symmetry of the M-N 4 moiety, resulting from its symmetrical planar structure, makes it chemically inert to a certain extent, thus reducing the kinetics of the catalytic reaction and hindering it. 39,132,135,136 Therefore, in order to tune the performance of M-N 4 active sites for eCO 2 RR, breaking the symmetrical electronic structure of M-N 4 via a reasonable adjustment of the coordination structure to optimize the electronic structure of the M-N 4 , and subsequently affecting the binding energies for eCO 2 RR intermediates have caught researchers’ attention and have been developed in full swing. By tuning the coordination numbers and introducing second atoms (metal or non-metal), the d orbital of the metal site can be significantly tuned, affecting the catalytic activity for eCO 2 RR.…”
Section: C1 Products On Mof-derived Sacsmentioning
confidence: 99%